Chaos control and function projective synchronization of fractional-order systems through the backstepping method - Das S.; Yadav V.K. (My University, 2025)
We study the chaos control and the function projective synchronization of a fractional-order T-system and Lorenz chaotic system using the backstepping method. Based on stability theory, we consider the condition for the local stability of nonlinear three-dimensional commensurate fractional-order system. Using the feedback control method, we control the chaos in the considered fractional-order T-system. We simulate the function projective synchronization between the fractional-order T-system and Lorenz system numerically using MATLAB and depict the results with plots. © 2016, Pleiades Publishing, Ltd.